A Porphyrin‐Based Conjugated Polymer for Highly Efficient In Vitro and In Vivo Photothermal Therapy. Issue 45 (27th September 2016) - Guo, Bing; Feng, Guangxue; Manghnani, Purnima Naresh; Cai, Xiaolei; Liu, Jie; Wu, Wenbo; Xu, Shidang; Cheng, Xiamin; Teh, Cathleen; Liu, Bin
Abstract : Conjugated polymers have been increasingly studied for photothermal therapy (PTT) because of their merits including large absorption coefficient, facile tuning of exciton energy dissipation through nonradiative decay, and good therapeutic efficacy. The high photothermal conversion efficiency (PCE) is the key to realize efficient PTT. Herein, a donor–acceptor (D–A) structured porphyrin‐containing conjugated polymer (PorCP) is reported for efficient PTT in vitro and in vivo. The D–A structure introduces intramolecular charge transfer along the backbone, resulting in redshifted Q band, broadened absorption, and increased extinction coefficient as compared to the state‐of‐art porphyrin‐based photothermal reagent. Through nanoencapsulation, the dense packing of a large number of PorCP molecules in a single nanoparticle (NP) leads to favorable nonradiative decay, good photostability, and high extinction coefficient of 4.23 × 10 4 m −1 cm −1 at 800 nm based on porphyrin molar concentration and the highest PCE of 63.8% among conjugated polymer NPs. With the aid of coloaded fluorescent conjugated polymer, the cellular uptake and distribution of the PorCP in vitro can be clearly visualized, which also shows effective photothermal tumor ablation in vitro and in vivo. This research indicates a new design route of conjugated polymer‐based photothermal therapeutic materials for potential personalized theranostic nanomedicine. Abstract : A porphyrin‐containing conjugated polymer is developed, which is further formulated into TAT‐decorated and 1, 2‐distearoyl‐ sn ‐glycero‐3‐phosphoethanolamine‐(polyethylene glycol) (DSPE‐PEG)‐encapsulated nanoparticles to serve as a photothermal reagent. The nanoparticles exhibit large molar absorptivity, excellent photostability, good biocompatibility, and high photothermal conversion efficiency, which have been successfully used for effective tumor ablation both in vitro and in vivo.